IMPACT OF COHERENCY ON THE PROCESS OF SPECTRAL COMPRESSION OF RANDOMLY MODULATED PULSES - Grigoryan, A.P. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The study of spectral compression of randomly modulated optical signals is reported. The study of the spectral compression process is carried out for the additive noise model for initial pulses with different coherence time. The studies show that the ratio of spectral compression increases with decreasing of the coherence time of the initial signal.